STUDI KASUS : IMPLEMENTASI ASUHAN KEPERAWATAN PADA NY.Y (G1P0A0) DENGAN MASALAH NYERI PUNGGUNG PADA TRIMESTER III KEHAMILAN - Laili Rizki Azzahra (2022)
Background: The third trimester is the gestation period from the seventh to the ninth month (28 weeks - 40 weeks). During the third trimester of pregnancy, one of the most common discomforts is back pain. Back pain in pregnant women can occur because along with the growth of the fetus in the mother's womb, the pelvic joints can move slightly to compensate for the enlargement of the fetus, the shoulders are pulled back and the lumbar is more curved, so the spinal joints become more flexible. The study was conducted to determine the factors that cause and how to treat back pain with nursing care to reduce the incidence of back pain in third trimester pregnant women. Methods: The design of this case study uses a simple descriptive method in the form of a case study in implementing nursing care for Ny. Y (G1P0A0) with back pain problems in the third trimester of pregnancy in the South Larangan neighborhood, Larangan District on 15 June - 18 June 2021. Data collection was carried out through home visits, interviews, observation, physical examinations and documentation. Results: The main nursing diagnosis was acute pain related to physiological changes, measuring pain scale with a numeric rating scale/NRS. The main nursing action taken in the form of pregnancy exercise to overcome the problem of back pain. Conclusion: This nursing care uses a pain scale measurement with a numeric rating scale/NRS and documentation with SOAP.